The effect of magnetic field and thermal relaxation on 2-D problem of generalized thermoelastic diffusion - Othman, M.I.A.; Farouk, R.M.; El Hamied, H.A. (Прикладная механика, 2013)
The generalized magneto-thermoelasticity is developed. The formulation is done under two theories: the generalized thermoelasticity coupled theory and Lord – Shulman theory with one relaxation time. The normal mode analysis is used to obtain the expres- sions for
temperature, displacement components, the thermal stresses distributions and concentration of diffusion. The variations of the considered variables are represented graphically. A comparison is made with the results predicted by two theories in presence and absence of the magnetic field. Розвинуто узагальнену теорію магнітотермопружності. Сформульовано задачу в
рамках двох підходів: теорії узагальненої зв’язаної термопружності та теорії Лорда – Шульмана з одним часом релаксації. Використано аналіз нормальної моди для отримання виразів для температури, компонентів зміщень, розподілу температурних напружень та концентрації дифузії. Зміну вказаних вище змінних представлено графічно. Порівняно результати в рамках обох теорій за умови наявності та відсутності магнітного поля.